Nutritional Strategies for Patients With Upper Gastrointestinal Cancers - Sang Hoon Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Patients with upper gastrointestinal tract cancers frequently develop severe malnutrition during treatment. Optimal nutritional management is imperative to enhance the efficacy of both chemotherapeutic and surgical interventions. In this article, various methods for nutritional screening and assessment, including a range of biochemical assays and decision-making frameworks relevant to clinical settings. We have described pre- and postoperative nutritional strategies and highlighted the established practical guidelines. Additionally, we investigated the key aspects of nutritional oversight during oncological treatment and emphasize the significance of a multidisciplinary approach that involves the services of physicians, dietitians, and nurses. We have outlined specific strategies to facilitate interprofessional collaboration in this setting.